(untitled) (Research, Society and Development, 2021)
Objective: To analyze the contributions of a university extension to the learning of health care for residents of Family and Community Health. Methodology: This is a research with a qualitative, descriptive and observational approach, composed of 8 residents participating in an extension project. The extension project, consists of the creation of conversation circles with therapists specialized in the care of Autism Spectrum Disorder, and its target audience is the community in general that is interested in the theme or who are caregivers of people with autism. The residents were interviewed, the data were recorded by the researcher and according to the Content Analysis proposed by Bardin16, in which they were transcribed in full and analyzed for the construction of the research. Results: According to the analysis of the testimonies, projects focused on this theme can contribute to prepare professionals for new challenges, in addition to contributing to the more humanized training of these professionals, since the testimonies arouse the need for a loving look at those who care. Conclusion: the experience contributed to generate reflections on the sensitivity of care to residents, allowing a look and attention to the needs of the community.